Game-based practice versus traditional practice in computer-based writing strategy training: effects on motivation and achievement - Proske, Antje; Roscoe, Rod D.; McNamara, Danielle S. (Educational technology research and development, 2014)
Achieving sustained student engagement with practice in computer-based writing strategy training can be a challenge. One potential solution is to foster engagement by embedding practice in educational games; yet there is currently little research comparing the effectiveness of game-based practice versus more traditional forms of practice. In this study, the ARCS model (Keller, Perform Instr 26(8):1–7, 1987b) was used to investigate the motivational characteristics of different practice conditions. To this end, 175 students were randomly assigned to one of four experimental conditions: game-based, question-based, model-based, and writing-based practice. All students first learned strategies to write an essay introduction. Subsequently, students practiced using the strategies in the four different conditions. Game-based practice was expected to positively affect ARCS-related motivation toward practice. Results showed that students perceived game-based practice as significantly more interesting and engaging than question-based practice. However, although game-based practice was perceived more positively, only model-based and question-based practice demonstrated a beneficial impact on students' ability to implement the writing strategies. These results underline the necessity of interconnecting motivational and instructional design when developing practice methods for computer-based writing strategy training.